The Effect of electrolyte concentration and temperature at electroplating with copper on the plate thickness and corrosion rate of plated gray cast iron - Muhammad Iksanudin; Rahmad D. Widodo; Deni F. Fitriyana; Ayub B. Anggoro (Jurnal Teknik Kimia, 2023)
This study aims to determine the effect of variations in electrolyte solution concentration and copper electroplating temperature on gray cast iron to achieve the desired copper layer thickness and reduce the corrosion rate of gray cast iron impeller pumps. A total of 30 test specimens made from gray cast iron were used, with dimensions conforming to the ASTM G31-72 standard for corrosion rate testing. The specimens were coated with copper electroplating using three different solutions: solution 1 (195 g/L copper sulfate, 45 g/L sulfuric acid), solution 2 (205 g/L copper sulfate, 50 g/L sulfuric acid), and solution 3 (215 g/L copper sulfate, 55 g/L sulfuric acid). Each solution was used with dipping temperatures of 30 – 34 °C, 40 – 44 °C, and 50 – 54 °C. After being coated with copper, the layer thickness was measured using a digital coating thickness gauge (F&NF type). The corrosion rate was then tested using the weight loss method, following the ASTM G31-72 standard, by immersing the specimens in seawater for 240 hours. The test results showed that the highest average thickness was achieved with solution 3 and a plating temperature of 50 – 54 °C, measuring 27.46 μm. The lowest average thickness was with solution 1 and a plating temperature of 30 – 34 °C, measuring 26.23 μm. The lowest corrosion rate was observed with solution 3 and a plating temperature of 50 – 54 °C, at 0.0041 mmpy, whereas the highest corrosion rate was found with solution 1 and a plating temperature of 30 – 34 °C, at 0.0079 mmpy. For comparison, the average corrosion rate of uncoated specimens was 2.2947 mmpy.